2016
DOI: 10.7600/jpfsm.5.313
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of individual muscle hardness and stiffness using ultrasound elastography

Abstract: Assessing muscle mechanical properties such as hardness and stiffness has important clinical implications. The use of ultrasound elastography to assess individual muscle hardness or stiffness has been increasing in recent years. Several different ultrasound elastography methods are currently in use, including strain elastography and shear wave elastography, which are capable of capturing the distribution of hardness and stiffness within individual muscles. In the present review, we outline some of the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…When the strain ratio is 1, the muscle hardness is identical to the reference; as stated in previous studies [5, 6], smaller strain ratios indicate harder muscle. The average value for the 10 images was used as the representative strain ratio.…”
Section: Case Presentationsupporting
confidence: 69%
See 1 more Smart Citation
“…When the strain ratio is 1, the muscle hardness is identical to the reference; as stated in previous studies [5, 6], smaller strain ratios indicate harder muscle. The average value for the 10 images was used as the representative strain ratio.…”
Section: Case Presentationsupporting
confidence: 69%
“…Recently, ultrasonic elastography has used for the measurement of individual muscle mechanical properties (e.g., muscle hardness) [5]. Muscle hardness measured using ultrasound strain elastography (USE) has been reported to be linearly related to muscle contraction intensity up to a moderate level of contraction, and USE is attracting attention as a method for estimating individual muscle strength (based on individual muscle hardness) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with conventional strain elastography, SWE is technically less operator-dependent as it largely relies on controlled ultrasound push beams rather than manually on tissue compression by sonographers for tissue deformation (Inami & Kawakami, 2016). It has also been proven to possess high intra-operator (ranging from 0.751 to 0.941) and moderate inter-operator reliability (0.585 and 0.749) in assessing the AT stiffness in both Chinese athletes and non-athletes, respectively (Chiu et al, 2016; Siu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The biceps brachii muscle hardness values obtained in the present study by PM (15.0–40.4 kPa) were in line with those in which PM was used to assess biceps brachii muscle hardness reported by Murayama et al 19 : 23.1 ± 6.5 kPa, and Komiya et al 6 : 30.4 ± 8.2 kPa. To the best of our knowledge, no previous study has reported YM of biceps brachii assessed by USE, but some studies used ultrasound shear wave elastography (USWE) that can evaluate YM based on the shear wave velocity (V): YM = 3pV 2 ( p = density: 1 g/cm 2 ) 27 . YM values of biceps brachii by USWE varied among the studies, but Akagi et al 28 reported 19.4 ± 6.8 kPa, and Nordez and Hug 29 reported 33.9 ± 11.4 kPa, which were in the range obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%